Contribution of Lewis X Carbohydrate Structure to Neuropathogenic Murine Coronaviral Spread - Kakizaki, Masatoshi; Togayachi, Akira; Narimatsu, Hisashi; Watanabe, Rihito (Japanese Journal of Infectious Diseases, 2016)
Although Lewis X (Lex), a carbohydrate structure, is involved in innate immunity through cell-to-cell and pathogen recognition, its expression has not been observed in mouse monocytes/macrophages (Mo/Mas). The Mo/Mas that infiltrate the meninges after infection with the neuropathogenic murine coronavirus strain srr7 are an initial target of infection. Furthermore, higher inflammatory responses were observed in gene-manipulated mice lacking α1,3-fucosyltransferase 9, which determines the expression of the Lex structure, than in wild type mice after infection. We investigated Lex expression using CD11b-positive peritoneal exudate cells (PECs) and found that Lex is inducible in Mo/Mas after infection with srr7, especially in the syncytial cells during the late phase of infection. The number of syncytial cells was reduced after treatment of the infected PECs with anti-Lex antibody, during the late phase of infection. In addition, the antibody treatment induced a marked reduction in the number of the infected cells at 24 hours post inoculation, without changing the infected cell numbers during the initial phase of infection. These data indicate that the Lex structure could play a role in syncytial formation and cell-to-cell infection during the late phase of infection.